PENERAPAN MINDFULLNESS BASED COGNITIVE THERAPY (MBCT) DALAM UPAYA MENURUNKAN KECEMASAN IBU HAMIL DI MASA PANDEMI COVID-19 - Christy N M Hitijahubessy; Cut Mutia Tatisina; Grenny Z. Rahakbauw (JURNAL ABDI MERCUSUAR, 2022)
Pandemic is an infectious disease that attacks the human respiratory system. This disease is especially susceptible to people over 60 years of age and those with weakened immune systems are at higher risk, including pregnant women. Mindfulness Based Cognitive Therapy is defined as a form of psychological therapy that provides attention in a specific way: intentionally, in the moment, and nonjudgmentally. MBCT is a process of accepting things as they are and approaching situations with an open mind reducing tension and fear and increasing trust. Mindfulness can provide support to mothers both during the perinatal period and beyond. Method : The method used in this activity is training with a service research strategy, namely one grub pre post test. The implementation time is from 7 to 15 November 2022 at the Christina M Tiahahu Health Center with the target being pregnant women. Result: The results show the successful achievement of PkM in increasing pregnant women's knowledge about pregnancy during the Covid-19 Pandemic, the dangers of anxiety in pregnancy and MBCT for pregnant women. This is proven through an increase in knowledge about Pregnancy during the Covid-19 Pandemic in the Good category from 20% to 57%, the dangers of anxiety in pregnancy in the Good category from 30% to 67% and MBCT for pregnant women in the good category from 3% to 44%. The statistical test results showed that there was a decrease in the anxiety of pregnant women after the MBCT intervention, where before the action the average participant had moderate to severe levels of anxiety and after the MBCT intervention their anxiety was in the mild and moderate category.